A Review and Analysis of Dialogue: Raymond Aron and Michel Foucault, Analyse de Jean-Francois Bert (2007) - Ali Abedi Renani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present paper aims to analyze the dialogue between Raymond Aron and Michal Foucault. A description of the two thinkers’ views was presented in order to understand the context in which the dialogue was taking place. The main issue between the two figures centers on the continuity or lack of continuity in historical periods. Aron criticizes Foucault’s account of epistemic breaks and defends interactions and partial continuities between historical periods. Although the two philosophers have structuralistic tendencies, their different ontology has divided them into this issue. Foucault in his archeology method does not seek continuity between events and periods, but seeks to show the disruptions that have been neglected. Aron criticizes the separation of epistemes and defends interaction between them. According to Aron, the world enjoys relatively fixed structures, which reveal themselves in different historic periods. Based on this view, he criticizes the subjective and relativistic views of Nietzsche and Weber.